Social justice in a tertiary education context: Do we practice what we preach?. (November 2018) - Gair, Susan; Baglow, Len
Concepts of social justice have strong historical roots, while more contemporary notions of social justice coincide with human rights, equity, fairness and facilitation of social change with lasting impact. In higher education, evident examples of social justice include widened university access facilitating a diverse student body and graduate workforce who can, in turn, contribute to a more just society. University student identity in past eras has been synonymous with social activism. Equally, social work has a mandate to uphold social justice. Yet tertiary students' own growing material hardships appear to constitute an unacknowledged injustice. While it is understood that tertiary study may mean short-lived poverty, more recent literature suggests that many university students are suffering mounting debt, increased mental health stress and vulnerability to withdrawal. In this article, the authors ponder social justice education by calling on specific results of a 2015 survey of 2320 Australian social work students. Findings revealed that for many students a juggling act of core study requirements, paid work, family commitments and affording necessities impacted their health, wellbeing and study success. Some astute students identified a disconnect between social work's staunch social justice agenda and its lack of acknowledgement, empathy or action regarding student hardship. The findings have implications for curricula, universities, accrediting bodies and educators who want to facilitate social justice education.